Vórtices no modelo sigma-O(3)-Maxwell-Chern-Simons-Higgs com acoplamento não mínimo - Cavalcante, Francisco Sales Ávila (1996)
In this work we consider an O(3) sigma model coupled nonminimally with an Abelian gauge field, whose dynamic is governed both by Maxwell and Chem-Simons terms. If the spontaneous symmetry breaking is taken place, we found that a new Maxwell as well as Chem-Simons term are generated, even with a generic Higgs potential. For a specific choice of this potential and a critical value of the nonminimal coupling constant there are both topological and nontopological self-dual soliton solutions, where the topological ones are considered. In addition, the introduction of a parameter in the Higgs potential allows the existence of asymmetric and symmetric phase. Static solitons of the vortices type satisfying the Bogomol'nyi bound are studied numerically and plotted.